Studi Komparatif Tingkat Efisiensi Emiten Konvensional Di Lq45 Dan Emiten Syariah Di JII Pada Bursa Efek Indonesia Tahun 2014 - Zainuddin Faqih, Aziz; , Drs. Triyono, M.Si (2016)
ABSTRACT Efficiency is one of the parameters used to measure an economic unit by looking at the ability of generating the optimal output using existing input. This research aims to analyze the level of efficiency For conventional LQ45 index and also analyze the level of efficiency of the Shariah index JII. Then analyze each efficiency comparison indexes, i.e. conventional indices (LQ45) compared with Islamic index (JII). Calculation based on DEA, on companies listed on the two firms LQ45 consistently experienced the efficiency, while on the JII perusaan there are three consistent experience efficiency. Then after the index compared between the two found no distinction on both the index during the first and second years of research, and on the remaining two periods namely diperiode third and fourth found differences between the two indices. Keywords: Input-Output, Data Envelopment Analysis, Comparison.